2023
DOI: 10.1021/acs.jafc.2c05670
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Yogurt Alleviates High-Fat Diet-Induced Lipid Accumulation and Insulin Resistance in Mice via the Adiponectin Pathway

Abstract: A high-fat diet (HFD) easily contributes to the pathogenesis of obesity and insulin resistance. Obesity and insulin resistance have been clinical and public health challenges all over the world. Probiotic-fermented yogurt is one type of popular and functional beverage in people’s daily lives. This study mainly explored the lipid- and glucose-lowering effects of Lactobacillus acidophilus NX2-6-fermented yogurt (LA-Y) in HFD-fed mice. The results showed that LA-Y administration improved the lipid profile in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Western blotting was performed as described by Tang. 81 The colon and prefrontal cortex of brain tissues (500 mg) were placed in a mortar along with liquid nitrogen and promptly crushed into powder. The powder was added to 500 μL of RIPA lysis buffer (10 μL mg −1 ) (Beyotime Biotech, Shanghai, China) containing PMSF and lysed on ice for 30 min after vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described by Tang. 81 The colon and prefrontal cortex of brain tissues (500 mg) were placed in a mortar along with liquid nitrogen and promptly crushed into powder. The powder was added to 500 μL of RIPA lysis buffer (10 μL mg −1 ) (Beyotime Biotech, Shanghai, China) containing PMSF and lysed on ice for 30 min after vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…182 Currently, yogurt fermented with Lactobacillus acidophilus NX2-6 has been demonstrated to lessen lipid deposition and insulin resistance in mice via the adiponectin pathway. 183 The alleviation of insulin resistance itself reduces androgen secretion. Adiponectin in the ovary is primarily produced by the surrounding fat pad, which significantly influences the production of sex steroid hormones in ovarian granulosa cells.…”
Section: Gut–fat–ovarian Axismentioning
confidence: 99%
“…Many studies have demonstrated the potential benefits of probiotic fermented yogurt, including its hypotensive, hypocholesterolemic, anti-diabetic, and anti-obesity properties, as well as its ability to reduce non-alcoholic fatty liver and improve intestinal health. [17][18][19] The research shows that the intake of yogurt fermented by Levilactobacillus brevis FZU0713 has changed the composition of the gut microbiota and increased the level of SCFAs. 20 Lacticaseibacillus rhamnosus fermented yogurt can enhance the nutritional value of yogurt, regulate the gut microbiota, and improve gut health.…”
Section: Introductionmentioning
confidence: 99%